2021
DOI: 10.1007/s40521-021-00286-y
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Bruton’s Tyrosine Kinase Inhibitors to Treat Allergic Disorders

Abstract: Purpose of review Studies show that inhibitors of Bruton’s tyrosine kinase (BTKis), currently FDA-approved for the treatment of B cell malignancies, can prevent IgE-mediated reactions through broad inhibition of the FcεRI signaling pathway in human mast cells and basophils. This review will summarize recent data supporting the use of these drugs as novel therapies in various allergic disorders. Recent findings Recent studies have shown that BTKis can prevent IgE-mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 51 publications
(58 reference statements)
0
21
0
Order By: Relevance
“…One recently completed Phase II clinical trial (NCT03149315) has tested the efficacy of ibrutinib on inhibiting food-induced anaphylaxis in adult patients. The initial results of this trial showed that short-term ibrutinib therapy (as few as 2 doses) suppresses skin test responses and eliminates IgE-mediated basophil activation in adults with peanut or tree nut allergy (59,128). Mechanistically, BTK is essential for FcϵRI signaling and allergic responses in human mast cells and basophils (59,(128)(129)(130)(131).…”
Section: Allergymentioning
confidence: 99%
See 3 more Smart Citations
“…One recently completed Phase II clinical trial (NCT03149315) has tested the efficacy of ibrutinib on inhibiting food-induced anaphylaxis in adult patients. The initial results of this trial showed that short-term ibrutinib therapy (as few as 2 doses) suppresses skin test responses and eliminates IgE-mediated basophil activation in adults with peanut or tree nut allergy (59,128). Mechanistically, BTK is essential for FcϵRI signaling and allergic responses in human mast cells and basophils (59,(128)(129)(130)(131).…”
Section: Allergymentioning
confidence: 99%
“…The initial results of this trial showed that short-term ibrutinib therapy (as few as 2 doses) suppresses skin test responses and eliminates IgE-mediated basophil activation in adults with peanut or tree nut allergy (59,128). Mechanistically, BTK is essential for FcϵRI signaling and allergic responses in human mast cells and basophils (59,(128)(129)(130)(131). Bone marrow-derived mast cells of Btk -/mice exhibit impaired FcϵRI-mediated production of eicosanoid, leukotriene C4 (LTC4) and reactive oxygen species (ROS) in vitro (132).…”
Section: Allergymentioning
confidence: 99%
See 2 more Smart Citations
“…Bruton's tyrosine kinase is an essential kinase for signaling through the high-affinity receptor FcεRI on the surface of mast cells and basophils, the activated signaling cascade causes the release of numerous allergic mediators including histamine, prostaglandins, leukotrienes, and cytokines responsible for inducing signs and symptoms in anaphylaxis [31].…”
Section: The Immunology Of Anaphylaxis and Pregnancy-brief Overviewmentioning
confidence: 99%